From Inflation to Growth : Eight Years of Transition - Doyle, Peter; Christoffersen, Peter (Washington, D.C. : International Monetary Fund, 1998)
This paper reexamines growth in transition using panel data to 1997. It suggests that output has been strongly affected by export market growth; that inflation has been associated with weaker output only above a threshold inflation rate; that structural reform has been associated with weaker output initially, but that it stimulates higher growth thereafter; and that rapid disinflation has been associated with output losses only in the presence of pegged exchange rates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet